Design Of A Setup For 3D Ultrasound Using Visual Probe Tracking - Ali, Aziah (2005)
3D ultrasound systems have been proven to offer some significant advantages over the conventional 2D ultrasound system. However , the costly nature of 3D ultrasound machines limits the availability of the technology in most of medical institutions. A cost effective method for generating 3D ultrasound images using the conventional 2D machine is proposed in this thesis.